Effect of Notoginsenoside R1 on reparative dentin formation via regulating the function of human dental pulp stem cells - Xuan He; Dan Liang; Xinyi Zhao; Kaixin Liu; Zicheng Zhang; Meiling Li; Xuemeng Ma; Wenxia Chen; Xiaoyi Zhong (Tissue and Cell, 2027)

Integrative multi-omics analysis reveals genetic and epigenetic regulatory networks of body weight in the mud crab (Scylla paramamosain) - Qionghui Qin; Weiren Zhang; Meiling Liang; Yijia Shih; Yaodong Zhang; Siyi Zhou; Kewei Huang; Xiaopeng Wang; Haihui Ye (Aquaculture, 2027)

Regional climate downscaling simulations for China since the Last Glacial Maximum - Naixin Cao; Liang Ning; Jian Liu; Zhengyu Liu; Mi Yan; Weiyi Sun; Meiling Jiang; Xueyuan Kuang; Huayu Lu; Kefan Chen; Yanmin Qin; Qin Wen; et al. (Science China Earth Sciences, 2026)

Aneuploid gametes produced by triploid Populus ‘Beilinxiongzhu 1#’ transmit higher paternal heterozygosity to progeny - Yaru Sang; Yunyun Xie; Yifan Zhao; Bo Kong; Dawei Cheng; Liang Li; Lexun Ma; Jiahua Du; Meiling Long; Dongliang Cao; Zhang Huajian; Lao Huiqi; et al. (Tree Genetics & Genomes, 2026)

Characteristics of the microbial carbon pump in kelp farming areas and the impact of artificial reefs: A metagenomic and ecological perspective - Junyang Ma; Jihua Liu; Zhansheng Guo; Meiling Zhu; Zitong Chai; Feng Jiang; Zhu Li; Zhenlin Liang; Zhaoyang Jiang (Environmental Research, 2026)

Solar-driven superhydrophobic modified polyurethane sponge for rapid in-situ recovery of oil and microplastics in marine oil spill co-contamination - Chuanliang Zhao; Sidan Peng; Bo Wu; Le Kang; Lanlan Liang; Meiling Liu; Liwei Yang; Wendong Wang; Xing Xu (Journal of Hazardous Materials, 2025)

The BBX Gene Family in Papaya (Carica papaya L.): Genome-Wide Identification and Expression Profiling During Fruit Ripening - Meiling Ding; Shengjie Li; Jialin Hu; Sicheng Bai; Xianqi Fu; Zhimiao Liang; Xiaomin Liang; Yating Li; Miaoyu Zhao (Tropical Plant Biology, 2025)

Self-assembled mogroside v nanomicelle system improves oral bioavailability of the magnolol - Chengzhi Liu; Lingyi Ren; Niu Liu; Mengchu Niu; Yifei Xiang; Xianhua Wu; Changhua Lin; Zhengmin Liang; Meiling Yu; Jiakang He (Food Chemistry, 2025)

Comparison of Meltpro Myco Assay with MALDI-TOF Mass Spectrometry for rapid and accurate detection of clinical Mycobacterium Species - Kehao Peng; Liuyue Xu; Xuezhi Wang; Jianming Hong; Gengchen Zhang; Yuchuan Zhao; Yinong Ye; Zengqi Huang; Jinmei Zhang; Yuchun Huang; Zhiqiao Wu; Xiaolin Yu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

The accumulation of microbial residues decreases with time after wetland-to-cropland conversion - Meiling Zhao; Guodong Wang; Yuanchun Zou; Lei Qin; Liang Yang; Ming Jiang (Applied Soil Ecology, 2025)

Calcium isotope composition of the Gangdese continental arc deep crust and implications for making continental crust - Meiling Wang; Zaicong Wang; Liang Guo; Zongqi Zou; Fei Wu; Wei Dai; Jingliang Guo; Kang Chen; Lanping Feng; Haihong Chen; Ming Li; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2025)

Low-temperature stress response: A transcriptomic study of the WRKY family in Prunus davidiana - Meiling Guo; Rongjun Pan; Zhenjing Chu; Wenxian Gai; Xuqiang Qiao; Meixia Liang (Cryobiology, 2025)

Characteristics, sources, and health risks of fine particulate matter in Wuhan subway, China - Ji-Liang Lü; Qing Han; Zhen Wang; Min Tao; Xun Hu; Meiling Cao; Qingzhu Huang; Mengdie Shi; Zhenyu He; Xiaohu Zhao (Science of The Total Environment, 2025)

Keystone taxa drive the synchronous production of methane and refractory dissolved organic matter in inland waters - Xinjie Shi; Wanzhu Li; Baoli Wang; Na Liu; Xia Liang; Meiling Yang; Cong-Qiang Liu (Water Research, 2025)

A new flocculant tannic acid for improving separation efficiency and lowering gas emissions from liquid and solid fractions of dairy slurry - Wenhua Liao; Yuan Bian; Chunjing Liu; Meiling Liu; Wenxu Liang; Zhiling Gao; Yanxia Gao; Jianzhi Xie (Journal of Cleaner Production, 2025)

Improving the functional components and biological activities of navel orange juice through fermentation with an autochthonous strain Lactiplantibacillus paraplantarum M23 - Meiling Huang; Chunling Lai; Yan Liang; Qin Xiong; Chaoyun Chen; Zhiran Ju; Yueming Jiang; Jun Zhang (Food and Bioproducts Processing, 2025)

Longitudinal relationship between built environment and physical fitness in Chinese children and adolescents: Findings from the COHERENCE study - Jinghong Liang; Shan Huang; Wenwen Bao; Yingqi Pu; Meiling Liu; Xiuzhi Yang; Zhuowen Wu; Jiaqi Chen; Guanghui Dong; Yajun Chen (Building and Environment, 2025)

Fermentation by Penicillium polonicum improves the functional components and biological effects of orange peel via producing β-glucosidase without the risk of potential mycotoxins - Yan Liang; Chunling Lai; Liangliang Gao; Qingna Wu; Meiling Huang; Yueming Jiang; Jun Zhang (Food Bioscience, 2024)

Coupled physicochemical dual-crosslinking Ti3C2T composite aerogels for the selective adsorption of gallium ions in acid fly ash leaching - Xiaopei Zhang; Weifeng Liu; Chang Liang; Dongju Fu; Meiling Wang; Xuguang Liu (Journal of Hazardous Materials, 2024)

A Profile of Drug-Resistant Mutations in Mycobacterium tuberculosis Isolates from Guangdong Province, China - Chenchen Zhang; Zhuhua Wu; Xinchun Huang; Yuchuan Zhao; Qi Sun; Yanmei Chen; Huixin Guo; Qinghua Liao; Huizhong Wu; Xunxun Chen; Anqi Liang; Wenya Dong; et al. (Indian Journal of Microbiology, 2024)

The role of cyclin-dependent kinase inhibitor 3 in the proliferation and migration of renal cell carcinoma - Chenbo Ni; Zhisheng Guo; Hengtao Bu; Xusong Zhao; Meiling Bao; Lei Ding; Chao Liang; Qingsheng Tang; Jie Li (Chemico-Biological Interactions, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

Green and efficient approach to extract bioactive flavonoids with antioxidant, antibacterial, antiglycation, and enzyme inhibitory activities from navel orange peel - Chunling Lai; Meiling Huang; Qin Xiong; Yan Liang; Yueming Jiang; Jun Zhang (Sustainable Chemistry and Pharmacy, 2024)

Comparative toxic effect of ammonia exposure on Mauremys sinensis and invasive species Trachemys scripta elegans - Li Ding; Zubin Huang; Lingyue Liang; Haitao Shi; Zhenhua Fang; Meiling Hong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Rice husk hydrochar prepared by hydrochloric acid assisted hydrothermal carbonization for levofloxacin removal in bioretention columns - Yidan Luo; Yuanwang Lan; Shuzhen Liang; Shuohan Yu; Mingshan Xue; Zuozhu Yin; Fang-Fang Shen; Xibao Li; Zhen Hong; Meiling Yan; Chan Xie; Bin Gao (Bioresource Technology, 2024)

Morphological and transcriptomic analyses of embryonic development of red-eared slider Trachemys scripta elegans - Jing Lin; Miaomiao Zhang; Fangbin Liang; Yunfang Ni; Jiani Zhang; Haitao Shi; Meiling Hong; Li Ding (Animal Reproduction Science, 2024)

Control of citrus blue and green molds by Actinomycin X2 and its possible antifungal mechanism - Liangliang Gao; Yan Liang; Qin Xiong; Meiling Huang; Yueming Jiang; Jun Zhang (Pesticide Biochemistry and Physiology, 2024)

Investigating the effects of organic amendments on soil microbial composition and its linkage to soil organic carbon: A global meta-analysis - Jiwen Cui; Binggeng Yang; Meiling Zhang; Dali Song; Xinpeng Xu; Chao Ai; Guoqing Liang; Wei Zhou (Science of The Total Environment, 2023)

Thermo-responsive ion imprinted polymer on the surface of magnetic carbon nanospheres for recognizing and capturing low-concentration lithium ion - Chang Liang; Xiaopei Zhang; Weifeng Liu; Xingfu Song; Shuying Sun; Dongju Fu; Geng Dong; Meiling Wang; Yonghui Bai; Xuguang Liu (Minerals Engineering, 2023)

Development and evaluation of diffusive gradients in thin-films technique with a novel titanium peroxide binding gel for in situ measurement of Tl in natural waters and sediments - Hongmei Deng; Meiling Liu; Zhaodong Liu; Minhua Su; Yue Gao; Danxing Yang; Yuxuan Liu; Liang Ma; Zhiqiang Yu; Tangfu Xiao; Jun Luo (Journal of Hazardous Materials, 2023)

The infertile individual analysis based on whole-exome sequencing in chinese multi-ethnic groups - Qiongzhen Zhao; Yanqi Li; Qi Liang; Jie Zhao; Kai Kang; Meiling Hou; Xin Zhang; Renqian Du; Lingyin Kong; Bo Liang; Weidong Huang (Genes & Genomics, 2023)

How do fish functional traits respond to dams at the global scale? - Meiling Chen; Yangyang Liang; Xinyu Cheng; Jun Wang; Liuyong Ding; Minrui Huang; Guojing Wang; Juan Tao; Chengzhi Ding (Hydrobiologia, 2023)

Partial substitution of manure reduces nitrous oxide emission with maintained yield in a winter wheat crop - Huizhou Gao; Yajing Xi; Xueping Wu; Xuexia Pei; Guopeng Liang; Ju Bai; Xiaojun Song; Meiling Zhang; Xiaotong Liu; Zixuan Han; Gang Zhao; Shengping Li (Journal of Environmental Management, 2023)

Plant Growth Regulators Enhance Saline–Alkali Tolerance by Upregulating the Levels of Antioxidants and Osmolytes in Soybean Seedlings - Minglong Yu; Qiong Wu; Dianfeng Zheng; Naijie Feng; Xilong Liang; Meiling Liu; Yao Li; Baomin Mou (Journal of Plant Growth Regulation, 2022)

Molecular mapping of candidate gene regulating fruit stripe trait in watermelon - Xiaoxue Liang; Meiling Gao; Sikandar Amanullah; Yu Guo; Hongguo Xu; Xiaosong Liu; Xiujie Liu; Jixiu Liu; Yue Gao; Chengzhi Yuan; Xuezheng Wang; Feishi Luan (Euphytica, 2022)

Morphological and endogenous phytohormone changes during long-term embryogenic cultures in Korean pine - Yan Liang; Xin Xu; Hailong Shen; Meiling Gao; Yan Zhao; Xue Bai (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Mechanism of interactions between α-conotoxin RegIIA and carbohydrates at the human α3β4 nicotinic acetylcholine receptor - Meiling Zheng; Han-Shen Tae; Liang Xue; Tao Jiang; Rilei Yu (Marine Life Science & Technology, 2022)
Conotoxins are marine peptide toxins from marine cone snails. The α-conotoxin RegIIA can selectively act on human (h) α3β4 nicotinic acetylcholine receptor (nAChR), and is an important lead for drug development. The high-resolution cryo-electron microscopy structure of the α3β4 nAChR demonstrates several carbohydrates are located near the orthosteric binding sites, which may affect α-conotoxin binding. Oligosaccharide chains can modify the physical and chemical properties of proteins by changing the conformation, hydrophobicity, quality and size of the protein. The purpose of this study is to explore the effect of oligosaccharide chains on the binding modes and activities of RegIIA and its derivatives at hα3β4 nAChRs. Through computational simulations, we designed and synthesized RegIIA mutants at position 14 to explore the importance of residue H14 to the activity of the peptide. Molecular dynamics simulations suggest that the oligosaccharide chains affect the binding of RegIIA at the hα3β4 nAChR through direct interactions with H14 and by affecting the C-loop conformation of the binding sites. Electrophysiology studies on H14 analogues suggest that in addition to forming direct interactions with the carbohydrates, the residue might play an important role in maintaining the conformation of the peptide. Overall, this study further clarifies the structure–activity relationship of α-conotoxin RegIIA at the hα3β4 nAChR and, also provides important experimental and theoretical basis for the development of new peptide drugs.

Genetic basis of maize ear angle revealed by high-density single nucleotide polymorphism markers in four recombinant inbred line populations - Jingwei Lin; Shoukun Li; Gengyuan Liang; Meiling Liu; Taicheng Jin; Zhengwei Qu; Haoge Li; Shuisen Chen; Cong Li; Ao Zhang; Yanye Ruan; Zhenhai Cui (Euphytica, 2020)

The inhibition of miR-17-5p promotes cortical neuron neurite growth via STAT3/GAP-43 pathway - Liang Zhang; Zhijie Wang; Bo Li; Ziwei Xia; Xin Wang; Yucai Xiu; Zheng Zhang; Chuanjie Chen; Hong Song; Wenhua Li; Mei Yu; Meiling Zhang; et al. (Molecular Biology Reports, 2020)

Round fruit shape in WI7239 cucumber is controlled by two interacting quantitative trait loci with one putatively encoding a tomato SUN homolog - Yupeng Pan; Xinjing Liang; Meiling Gao; Hanqiang Liu; Huanwen Meng; Yiqun Weng; Zhihui Cheng (Theoretical and Applied Genetics, 2017)

Characterization of BcMF23a and BcMF23b, two putative pectin methylesterase genes related to pollen development in Brassica campestris ssp. chinensis - Sue Lin; Li Huang; Xiaolin Yu; Xingpeng Xiong; Xiaoyan Yue; Tingting Liu; Ying Liang; Meiling Lv; Jiashu Cao (Molecular Biology Reports, 2017)

A comparative analysis of the evolution, expression, and cis-regulatory element of polygalacturonase genes in grasses and dicots - Ying Liang; Youjian Yu; Jinlong Cui; Meiling Lyu; Liai Xu; Jiashu Cao (Functional & Integrative Genomics, 2016)

Dissecting the complex molecular evolution and expression of polygalacturonase gene family in Brassica rapa ssp. chinensis - Ying Liang; Youjian Yu; Xiuping Shen; Heng Dong; Meiling Lyu; Liai Xu; Zhiming Ma; Tingting Liu; Jiashu Cao (Plant Molecular Biology, 2015)

Identification and expression analysis of BoMF25, a novel polygalacturonase gene involved in pollen development of Brassica oleracea - Meiling Lyu; Ying Liang; Youjian Yu; Zhiming Ma; Limin Song; Xiaoyan Yue; Jiashu Cao (Plant Reproduction, 2015)

Molecular Cloning and Characterization of a Novel Polygalacturonase Gene, BcMF24, Involved in Pollen Development of Brassica campestris ssp. chinensis - Youjian Yu; Meiling Lv; Ying Liang; Xingpeng Xiong; Jiashu Cao (Plant Molecular Biology Reporter, 2014)

Effects of temperature and organic and inorganic nutrients on the growth of Chattonella marina (Raphidophyceae) from the Daya Bay, South China Sea - Zhaohui Wang; Meiling Yuan; Yu Liang; Songhui Lu (Acta Oceanologica Sinica, 2011)